Effect of Anti Diuretic Hormon (ADH) in Kidney Function on Post Hemodialysis End Stage Renal Failure Disease (ESRD) Iraqi Patients - Al-Taiee, Tiba A. Kh.; Al-Shammaa, Nawal M.J (Iraqi Journal of Science, 2018)
Chronic renal disease (CRD) is a patho-physiologic process with multiple etiologies, resulting in the inexorable attrition of Nephron number and function and frequently leading to end-stage renal disease (ESRD). In turn, ESRD represents a clinical state or condition in which there has been an irreversible loss of endogenous renal function, of a degree sufficient to render the patient permanently dependent upon renal replacement therapy (dialysis of transplantation) in order to avoid life threatening uremia. The current study was applied on 80 patients, the age range within 25-70 years, selected sample of patients who attend Iraqi center of kidney dialysis, Baghdad Teaching Hospital and Al-Yarmok Teaching Hospital . All the patients body mass index [BMI] were measured. Serum anti diuretic hormone ADH was assessed using enzyme linked immunosorbent kit [Elisa], and urea, creatinine, albumin, hemoglobin were determined by spectrophotometer (PD-303), and sodium, potassium, chloride were determined by Electrolyte analyzer. The study patients were divided into two groups : GA include the healthy subjects as a control and GB include the post dialysis ESRD patients . The results showed a highly significant increase in ADH , Urea and Creatinine levels in GB when compared with the control and highly significant decrease in albumin and hemoglobin levels in GB when compared with the control. Non -significant decrease in sodium and potassium levels in GB when compared with the control, while highly significant increase in chloride level in GB when compared with the control.